(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Ranked as the fourth most prevalent cancer among women globally, cervical cancer presents a significant concentration of 90% of cases in low- and middle-income countries. The potential for preventing cervical cancer through vaccination is substantial. However, the implementation of the human papillomavirus (HPV) vaccine encounters challenges, including acceptance barriers, lack of awareness, and high vaccine costs. Overcoming these obstacles is crucial, especially in regions like India, where cervical cancer screening is a significant concern. The objective is to assess the comprehension, viewpoints, and utilization of the HPV vaccine among medical students enrolled in a medical college. Material and Methods: A descriptive cross-sectional study was conducted among 384 study subjects using a pre-tested, semi-structured questionnaire. Results: Perspectives on HPV vaccine administration ranged, with 55% advocating its use in the 10-30 age range. Opinions diverged on vaccine eligibility for boys, administration to sexually active girls, and the necessity of HPV screening before vaccination. Concerns about vaccine safety, administration to HPV-infected women, and cervical cancer screening post-vaccination exhibited considerable diversity. Conclusion: Provides critical insights into medical students’ attitudes and awareness regarding HPV and vaccine, highlighting the significance of tailored health education initiatives to address knowledge gaps and misconceptions. Recognizing these diverse perspectives can guide the development of targeted strategies to enhance public acceptance and utilization of the HPV vaccine. This research contributes to shaping informed decision-making among future healthcare professionals, laying the groundwork for improved public health outcomes.